Wednesday

January 28, 2015

January 28, 2015

Posted by **Jade** on Monday, March 4, 2013 at 4:09pm.

Sum (infinity, n=1) 1/(1+e^-n)

Sum (infinity, n=1) (2*4*6...2n)/n!

Sum (infinity, n=0) (n-6)/n

Sum (infinity, n=0) (n-6)/n!

Sum (infinity, n=0) (100n^14)/4^n

**Answer this Question**

**Related Questions**

CALC 2 - a. Consider the following limit as a fact: lim n-> infinity ((n!)^1/...

calculus - find the sum of the series: 1. the sum from n=1 to infinity of ((-1)^...

Calc 2 - Use the ratio or the root test to determine the convergence of the ...

Calculus - Determine convergence of divergence. If convergent, find the sum. Sum...

calculus - Determine whether the series is convergent o divergent and say what ...

calculus - determine whether the series is convergent if so find sum: the sum of...

Calc II - Use the comparison or limit comparison test to decide if the following...

calculus - test the series for convergence or divergence. the sum from n=1 to ...

calculus - test the series for convergence or divergence. the sum from n=1 to ...

calculus - true or false: if the sum from n=1 to infinity of a(n) converges, and...